Occurrence of root rot caused by Fusarium fujikuroi and Fusarium proliferatum on peanut in China - Sun, Wei (Plant disease, 2022)
Root rot of peanut, caused by Fusarium spp., is a devastating disease in most peanut cultivation regions. In this reported outbreak, Fusarium root rot of peanut has been observed in Henan province, China in July 2021. About 20% of peanuts in a field (0.66 ha) were affected. Early symptoms comprised the wilt of the lower leaves, and the darkening of the vascular tissue of roots, which turned brown. Progressively, the whole plant wilted, the roots rotted, and the plant ultimately died. Pathogenic species were isolated from plants showing symptoms of root rot in the field. A total of 206 Fusarium isolates were generated, and 16 isolates were preliminarily identified as Fusarium fujikuroi based on morphological characteristics. Isolates were obtained and grown on PDA plates. Isolates developed floccose white aerial mycelia with reddish-pink coloration in the medium in 2 weeks on the benchtop. Macroconidia were 3-5 septate, measuring 27.5 to 48.8 × 2.6 to 3.8 μm (avg. 36.7 × 3.6 μm, n=50). Microconidia were abundant in chains, mainly asepatate, oval to kidney-shaped, 4.0 to 11.6 × 2.5 to 4.1 μm (avg. 5.8 ×3.1 μm, n=50). DNA was extracted from mycelium and the following genes were amplified and sequenced: the internal transcribed spacer (ITS) region using ITS1/ITS4 primers (White et al.1990) (Genbank assessions MZ831304 to MZ831308), the partial calmodulin gene (CAM, primer CL1/CL2A, O'Donnell.)(Genbank assession MZ856333 to MZ856337) and the partial translation elongation factor (EF-1α) using primer EF1/EF2 (Geiser et al.)(Genbank assession MZ856338 to MZ8564342). FUSARIUM-ID analysis showed 98.18% to 100% similarity with sequences of the F. fujikuroi species complex. The phylogenetic analysis was conducted using a neighbor-joining algorithm based on the ITS, CAM, and EF-1α gene sequences. The isolates were clustered with F. fujikuroi clade (Supplementary Fig.1). Koch's postulates were conducted using a sand-cornmeal-inoculum-layer method (Bilgi et al.). Briefly, 400 ml plastic boxes were filled with 15g of sterilized premium-grade coarse vermiculite, followed by a 15 g of inoculum prepared as sand-cornmeal mixture inoculum. The inoculum for each F. fujikuroi isolates was prepared by infesting a pre-sterilized sand-cornmeal mixture with three 5 mm plugs of cultures. Three F. fujikuroi isolates and PDA plugs were inoculated to serve as positive control and non-inoculated control treatments, respectively. The completed colonization of the sand-cornmeal mixture was finished by incubating at 25 ℃ for 7-10 days. Eight pre-germinated seeds of cv. Luhua No.1 was then covered with another 8 g of vermiculite. Peanuts were grown at 25 °C with 85% relative humidity under a light/dark cycle of 14h/10h. After 14 days of incubation, the inoculated plants showed typical symptoms of root rot similar to those in the field: pre-emergence damping-off, reddish-brown lesions on the tap, and lateral roots. F. fujikuroi was successfully re-isolated from inoculated plants but not from the controls and identified as described above. F. fujikuroi was reported to cause bakanae disease of rice (Amatulli et. al.), and root rot of soybeans (Zhao et. al.). To the best of our knowledge, this is the first record of F. fujikuroi causing root rot of peanut in China